2015
DOI: 10.2214/ajr.14.13914
|View full text |Cite
|
Sign up to set email alerts
|

Extraosseous Findings on Bone Scintigraphy Using Fusion SPECT/CT and Correlative Imaging

Abstract: We present examples of extraosseous radiotracer uptake seen on (99m)Tc-MDP bone scans in which either SPECT with integrated CT or correlative imaging improved the study's interpretation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
33
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 48 publications
3
33
1
3
Order By: Relevance
“…However, because most patients that underwent bone scintigraphy had a history of cancer or suspected tumors, the population enrolled in this study was biased to a certain extent, which might have resulted in a higher proportion of malignant tumors. Previous studies suggested that the mechanisms of the neoplastic uptake of MDP were mainly related to necrosis and/or calcification, a rich blood supply and the osteoid matrix in tumors, 9 which was also supported by our study based on the findings of CT, MRI, ultrasound etc. : 28 (28/33, 84.8%) pediatric and 22 (22/31, 71.0%) adult tumors had varying degrees of necrosis and/or calcification in the lesions.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, because most patients that underwent bone scintigraphy had a history of cancer or suspected tumors, the population enrolled in this study was biased to a certain extent, which might have resulted in a higher proportion of malignant tumors. Previous studies suggested that the mechanisms of the neoplastic uptake of MDP were mainly related to necrosis and/or calcification, a rich blood supply and the osteoid matrix in tumors, 9 which was also supported by our study based on the findings of CT, MRI, ultrasound etc. : 28 (28/33, 84.8%) pediatric and 22 (22/31, 71.0%) adult tumors had varying degrees of necrosis and/or calcification in the lesions.…”
Section: Discussionsupporting
confidence: 90%
“…Otherwise, MDP uptake was mostly found in lung cancer (11/31, 35.5%) in adults, followed by liver metastases from the gastrointestinal tract and breast (9/31, 29.0%), which was basically consistent with previous reports. 9 Our study also confirmed that the extraosseous soft tissue tumors that accumulated MDP were likely to be malignant. Altogether, neoplastic uptake was observed in 63 pediatric (32/33) and adult (31/31) malignant tumors, with the exception of one pediatric benign vascular tumor.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Palavras-chave: acidente vascular cerebral, cintilografia óssea, captação extra óssea. 1 Universidad CES. ORCID: 0000-0002-4373-3787.…”
unclassified